Results of a Pilot Randomized Placebo-Controlled Trial in Primary and Secondary Raynaud's Phenomenon with St. John's Wort: Detecting Changes in Angiogenic Cytokines When RP Improves. (12th September 2011) - Malenfant, Déanne; Summers, Kelly; Seney, Shannon; McBain, Donna; Petrlich, Lisa; Watson, Sharon; Vanderhoek, Louise; Samadi, Nooshin; Bonner, Ashley; Pope, Janet
Abstract : Objectives .To perform a 6-week double-blind RCT in Raynaud's phenomenon (RP) comparing the plant extract St. John's Wort (SJW) to placebo. Methods . RP patients having at least 7 attacks per week were stratified by primary and secondary RP and within secondary by systemic sclerosis or other connective tissue disease. Subjects completed a daily standardized diary recording all RP attacks (frequency, duration and severity). Serum levels of 18 inflammatory and angiogenic cytokines were measured pre- and post-treatment. Results . Eighteen patients completed the study; 8 received SJW and 10 placebo. The decrease in mean number of attacks per day was 0.75 with SJW and 1.01 with placebo, P = 0.06 . Attack duration and severity were not different between groups. Cytokine analyses demonstrated no between-groups differences. Combining treatment groups, those with >50% improvement in frequency of attacks yielded a significant increase in E-selectin (P = 0.049 ), MMP-9 (P = 0.011 ), G-CSF (P = 0.02 ), and VEGF (P = 0.012 ) pre- versus post-treatment. A ≥50% improvement in severity of attacks corresponded to a significant increase in levels of sVCAM-1 (P = 0.003 ), sICAM-1 (P = 0.007 ), and MCP-1 (P = 0.004 ). Conclusions . There were no clinical or biomarker benefit of SJW versus placebo in RP. However, combining all patients, there were changes in some cytokines that may be further investigated.